Effect of substrate temperature on crystalline structure and galvanomagnetic characteristics of Ni—Cu alloy thin films - Loboda, V.B.; Pirogova, S.N.; Saltykova, A.I. (Functional Materials, 2006)
The phase composition, crystalline structure and magnetoresistance of the Ni-Cu alloy thin films of various thickness and concentrations have been studied. Influence of substrate temperature on the crystalline structure formation processes and phase composition of the films has been considered. Dependences of magnetoresistance ΔR/R₀ and coercive force Нс on the substrate temperature have been established.